Две судьбы: роман / Семен Малков - Малков Семен Наумович (Гелиос, 2003)
Экземпляры: (20240502) / Инвентарный номер: 29650 / Цена: 92.68 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 19 / ГРНТИ: 17 / ББК: 84(2=411.2)6